The Scaling of Relaxation Processes (Advances in Dielectrics,, 2018)
The dielectric properties especially of glassy materials are nowadays explored at widely varying temperatures and pressures without any gap in the spectral range from μHz up to the Infrared, thus covering typically 20 decades or more. This extraordinary span enables to trace the scaling and the mutual interactions of relaxation processes in detail, e.g. the dynamic glass transition and secondary relaxations, but as well far infrared vibrations, like the Boson peak. Additionally the evolution of intra-molecular interactions in the course of the dynamic glass transition is also well explored by (Fourier Transform) Infrared Spectroscopy. This volume within 'Advances in Dielectrics' summarizes this knowledge and discusses it with respect to the existing and often competing theoretical concepts.